PENGARUH KECERDASAN EMOSIONAL TERHADAP KEDISIPLINAN BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Edyta Darmayanti; Ferdinandus Etuasius Dole; Maria Kristina Ota (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
The problem raised in this study is how the level of Emotional Intelligence of SDI Onekore 06 students, how is the level of learning discipline of SDI Onekore 06 students and whether there is an effect of emotional intelligence on student learning discipline at SDI Onekore 06. The purpose of this study is to determine the effect Emotional intelligence on the learning disciplines of SDI Onekore 06 students. This study used correlational quantitative research, which was conducted at SDI Onekore 06, Ende Tengah District, Ende Regency. The sample of this research was students in grades V and VI, who were taken using purposive sampling technique. Data were collected through a questionnaire. Hypothesis testing uses Simple Linear Regression analysis with the Pearson Product Moment Correlation formula. The results of this study indicate that the level of emotional intelligence tends to be high with an average of 94.5 and the level of discipline tends to be high with an average of 93.50. There is a significant influence between emotional intelligence on learning discipline. This can be seen from the results of statistical analysis which shows the correlation coefficient (r) of 0.419 which states that the correlation index (r) X to Y is sufficient with an effect of 17.6% and Sig = 0.014 at the significance level alpha ( = 0.05)